Budgetary and tax policy at the present stage and its role in forming budgets of different levels - N. Z. Zotikov (Управление)
Budgetary and tax policy is designed to ensure sustainable development of the Russian economy on the basis of modernization, to improve the living standards of the population by reducing social inequality, and to adapt the budget system to modern realities. The sanctions imposed by the European Union and the United States of America against Russia affect not only the production sphere, but also economy as a whole. The decline in oil prices, ruble devaluation, and outﬂow of foreign capital eventually lead to budget deficit. In these conditions, budgetary and tax policy remains one of the most important instruments of the economic policy pursued by the state. Increasing tax system efficiency becomes a priority. The objectives of the study include establishing budgetary and tax system effectiveness in forming budget revenues of different levels, including administrative centers (capitals of republics, regional centers). The article uses analysis and synthesis, generalization, grouping, dynamics, comparison, tabular method, and data of the Federal State Statistics Service, the Ministry of Finance of the Russian Federation, and the Federal Tax Service of the Russian Federation. It has been established that the existing budget and tax policy does not provide regional and local budgets with necessary financial resources as they are dominated by inter-budget transfers that cover only their deficit and do not ensure economic growth. All this predetermines the need to redistribute tax revenues in favor of regional and local budgets that will weaken the share of inter-budget transfers in these budgets.